2017
DOI: 10.1021/acs.langmuir.7b02839
|View full text |Cite
|
Sign up to set email alerts
|

Unoccupied Interface and Molecular States in Thiol and Dithiol Monolayers

Abstract: The electronic structure of self-assembled monolayers (SAMs) formed by thiols of different lengths and dithiol molecules bound to Au(111) has been characterized. Inverse photoemission spectroscopy (IPES) and density functional theory have been used to describe the molecule/Au substrate system. All molecular layers display a clear signal in the IPES data at the edge of the lowest unoccupied system orbital (LUSO), roughly 3 eV above the Fermi level. There is also evidence, in both the experimental data and the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 56 publications
4
12
0
Order By: Relevance
“…Furthermore, the kinetics for thermally induced thiol release should be hindered on this time scale . Tunneling spectroscopy experiments of thiolated self-assembled monolayers (SAMs) on Au(111) have recently shown that in the range of ∼1.2 to ∼1.4 eV above the Fermi level there exist unoccupied states, derived from the Au–S hybridization and induced by the strong coupling of S to the Au substrate. , This range of energies perfectly matches the energy of the photons employed in our experiments, suggesting that those states could be involved in our hot-electron-induced desorption process.…”
Section: Resultssupporting
confidence: 77%
“…Furthermore, the kinetics for thermally induced thiol release should be hindered on this time scale . Tunneling spectroscopy experiments of thiolated self-assembled monolayers (SAMs) on Au(111) have recently shown that in the range of ∼1.2 to ∼1.4 eV above the Fermi level there exist unoccupied states, derived from the Au–S hybridization and induced by the strong coupling of S to the Au substrate. , This range of energies perfectly matches the energy of the photons employed in our experiments, suggesting that those states could be involved in our hot-electron-induced desorption process.…”
Section: Resultssupporting
confidence: 77%
“…Figure 1 e(i) shows the S 2p spectrum of the BHT on cold Ag(111), which was kept at 170 K during deposition and the XPS measurement. The two peaks of S 2p 3/2 at 163.5 eV and 161.7 eV are assigned to intact thiol [36][37][38][39][40] and thiolate, [23] respectively. This reveals the partial deprotonation of BHT has already occurred at 170 K. The dehydrogenation occurring during thermal evaporation can be ruled out, since the S 2p spectrum of the BHT powder already used for the deposition in STM experiments is the same as that of the pristine BHT powder ( Figure S6).…”
mentioning
confidence: 99%
“…The chemical states of the TCNs on Cu(111) surface was studied by XPS ( Figure 4). On the sample prepared at 170 K (Figure 4 a), the S 2p 3/2 peaks at 163.7 eV and 162.1 eV are assigned to intact thiol groups [36][37][38][39][40] and thiolate groups, [42] respectively. The higher intensity of the thiolate species reveals that the deprotonation of thiol groups are much easier on Cu (111) than on Ag(111).…”
mentioning
confidence: 99%
“…47 In our experiments, the energy range -set by the excitation wavelengths (~1.3 to ~1.6 eV) -matches the energy range of unoccupied Au-S states (~1.2 to ~1.4 eV above the Fermi level). 48,49 On the other hand, the density of electrons is given by the resistive losses of the structure, meaning that regions with higher resistive losses will be more reactive -if they have enough energy to react -as it has been recently shown. 39,50 In the particular case of thiol desorption, resistive losses scale linearly with the fs irradiation fluence, 39 implying that different super-resolution absorption maps can be obtained depending on the fluence of the femtosecond laser irradiation (see for example Figure S6).…”
mentioning
confidence: 99%